APLICAÇÃO PÓS-COLHEITA DE RESVERATROL EM FRUTOS DE CAQUI “FUYU” E “GIOMBO” (Diospyrus kaki L.) - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
Knowing about the perishability of the persimmon, the raising of the production and the high losses after harvest of this product it was needed to evaluate the effect of the after harvest treatment in water solution of resveratrol. The research was done at the University of Ponta Grossa Vegetable Biotechnology Lab in april/march of 2007. The fruits were immerse during five seconds in water solution of resveratrol in doses of 1000;2000 and 3000 mg.L-¹ to cultivate Fuyu and in doses of 4000;5000 and 6000 mg.L-¹ to cultivate Giombo. The fruits were stocked in a cold chamber at 0±2º C and ur 95±2%. The Fuyu fruits stood stocked for 0;15;30 and 45 days and the Giombo fruits for 0; 7; 15; 21 and 28 days and then took off refrigeration and maintaned for 2 days in a aclimation chamber at 25ºC to simulate the comercial environment. The fruits were evaluated on weight loss, fortitude, total soluble solids, pulp Ph, total acidity and vitamin C. It was observed that the resveratrol didn't preserve the pulp fortitude and didn't maintain the Giombo or Fuyu fruits weight. The soluble solids grade varied from 16 to 22ºBrix and the acidity of the fruits varied from Fuyu to Giombo. The pH value from the Giombo fruits stayed in the range of 5,13 to 5,54 , and the Fuyu fruits between 5,0 and 5,92. The resveratrol treatment affected in a negative way the vitamin C grades.
Keywords: resveratrol; firmeza de polpa; armazenamento qualidade de fruto; resveratrol; pulp fortitude; stocking; fruit quality; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA